Relationship between the intellectual diagnosis and social development in mild mentally retarded and borderline children - Sótil de Pacheco, Amparo (2000)
The present study is fruit of the professional experience during years, in the treatment of children and teenagers with educable mental retardation that study in the Center of Special Education N° 06. It seeks to be a contribution to the exact knowledge of the problem of the student with mental retardation, regarding the relationship between intelligence and social adaptation. The Educational System through the modality of Special Education, comes implementing the opening of Shops where labor training is imparted to the students, in order to qualify them in the acting of a labor activity it specifies that it is what facilitated the rehabilitation of the exceptional one by means of their economic integration to the society, allowing them to find a life with sense and worthy of a human being. Keeping in mind the complexity to select, to locate and to train in a compatible shop with their aptitudes, interests and potentialities, it is necessary to have methods and valid and reliable procedures that allow a scientific approach to the knowledge and solution of the outlined problems.